Influence of Broadcast Nozzle Design and Weed Density on Dicamba Plus Glyphosate Deposition, Coverage, and Efficacy in Dicamba-Resistant Soybean - Kramer, Madison D.; Legleiter, Travis R. (Frontiers in Agronomy, 2022)
Dicamba injury to sensitive soybean and other broadleaf crops due to drift is a major issue. Dicamba label restrictions have been created to mitigate the off target movement of dicamba. One restriction is the mandated use of low drift nozzles to spray dicamba; these nozzles produce large droplet spectrums and minimize the production of driftable fines. Experiments were conducted to evaluate herbicide coverage, deposition, and efficacy as influenced by spray nozzle design and density of waterhemp, goosegrass, and large crabgrass in dicamba-resistant soybean. Dicamba plus glyphosate was applied to 5- to 10-cm tall weeds with a Turbo TeeJet (TT11005) nozzle and two drift reduction nozzles approved for dicamba applications: Turbo TeeJet Induction (TTI11005) and Pentair Ultra Lo-Drift (ULD12005). Weed densities were categorized into different levels and established in a 0.25 m2 quadrat prior to postemergence application. Deposition of herbicide spray solution onto targeted weeds was not different despite coverage differences observed on Kromekote spray cards. Coverage of herbicide solution was consistently lower with the low drift TTI11005 nozzle as compared to the TT11005 nozzle. Herbicide efficacy on waterhemp plants was lowest at the highest waterhemp densities of 54 plants per m2 with the drift reducing TTI11005 nozzle. Although weed control was not lowered at any density when applications were made with the ULD nozzle as compared to the TT11005 nozzle. Additionally, herbicide efficacy was reduced as large crabgrass density increased. Overall, the use of a drift reducing nozzle can be successful for waterhemp control and Poaceae control postemergence in soybean when weed densities are suppressed or reduced through methods such as the use of a residual preemergence herbicide or cereal rye cove crop.